Analisis Pengaruh Produksi, Harga Ekspor Crude Palm Oil, Nilai Tukar IDR/USD Terhadap Volume Ekspor Crude Palm Oil Indonesia 2012-2016 - Hamzah, Rifan Nur; Santoso, Ismanto Hadi (Economie: Jurnal Ilmu Ekonomi, 2020)
Crude Palm Oil is a commodity that is quite instrumental in the results of Indonesian plantations because it has a fairly large production yield and export quantity in meeting the needs of the world's crude palm oil. Indonesia is a country as the largest producer and exporter of crude palm oil in the world because Indonesia has vast plantations in tropical countries. This study aims to determine the effect of CPO production, CPO prices, CPO consumption levels, IDR / USD exchange rates on Indonesia's CPO export volume. The analytical method used in this research is to use quantitative methods using secondary data. To estimate the effect of independent variables on the dependent variable, multiple linear regression analysis is used with time series data between 2012-2016. The results showed that CPO production and the level of CPO consumption had a positive effect on Indonesia's CPO export volume, and the CPO price and IDR / USD exchange rate had a negative effect.